Item non-response rates: a comparison of online and paper questionnaires - Denscombe, Martyn (International journal of social research methodology, 2009)
Item non-response rates are a significant factor affecting the quality of questionnaire data. This article looks at the impact that the mode of administration might have on item non-response rates. Using closely matched groups of respondents (n = 466) it compares item non-response rates for near-identical versions of online and paper questionnaires. The research also analyses the difference between fixed-choice and open-ended questions in terms of their respective item non-response rates. Findings from the research indicate that the administration of questionnaires online, while it might have relatively little impact on the item non-response rates for fixed-choice questions, would seem to reduce item non-response rates where the questions are open-ended and require respondents to provide unstructured text-based answers.